IMPLEMENTATION OF ACADEMIC SUPERVISION OF PRINCIPALS IN IMPROVING LEARNING QUALITY AT BABAHROT'S STATE SCHOOLS - Muhammad Adli; Nasir Usman; Niswanto (CV. RADJA PUBLIKA, 2024)
The quality of learning in schools is an important factor in educating the nation's life. Academic supervision by school principals is an effort made to improve the quality of learning. The purpose of this study was to describe the implementation of the academic supervision program by school principals in improving the quality of learning in public primary schools in Babahrot District, Southwest Aceh Regency. The research method used is descriptive with a qualitative approach, using interviews, observations, and documentation studies as data collection techniques. The results showed that: (1) The academic supervision program is prepared at the beginning of the semester in teacher meetings, adjusted to the actual situation in each school, with a focus on planning, implementation, and evaluation of learning; (2) The implementation of the program involves three stages: pre-observation meetings, classroom observations, and post-observation meetings, using a collaborative approach and individual and group techniques; (3) Principals conduct follow-up by analyzing and evaluating the results of observations on an ongoing basis; (4) Obstacles include many other activities that interfere with the supervision schedule, lack of interest and motivation to become a supervisor, and lack of knowledge and skills related to academic supervision. Lack of commitment from principals and teachers is also an obstacle in supporting the implementation of academic supervision.